LEARNING A FOREIGN LANGUAGE DEVELOPS TO LERANCE - Rustamova, Shahnoza; Turg`unova Fazilat Rustam qizi (Журнал иностранных языков и лингвистики, 2023)
Our article explores and analyzes how students should be tolerant, optimistic and consistent with each other when learning foreign languages ​​alongside language learning. By learning foreign languages, they get to know another culture. Maintaining world peace is very important and it is through tolerance that we can achieve this.